A rare scenario of perforated gastrointestinal stromal tumours of ileum - Shankar, Mrinal; Ravindra, K.; R., Manju; Ramchandani, Radhakrishna (International Surgery Journal, 2020)
Gastro-intestinal stromal tumours (GIST) are among the common mesenchymal tumours of the gastro-intestinal (GI) tract. It varies in location and presentation. GIST are reported in the stomach frequently (60-70%), followed by small intestine (20-25%). Mainly GIST manifest typically with bleeding or vague abdominal pain and discomfort. The spontaneous perforation of GIST is very rare. We report case of a middle-age male patient who presented in emergency with pain in right lower abdomen associated with features of peritonism. After clinical evaluation and preliminary radiological investigations, a working diagnosis of perforated appendix was made. Patient was undertaken for emergency surgery. A diagnostic laparoscopy followed by midline laparotomy was done. Intra-operatively, a perforated and necrotic outpouching at antimesenteric border of terminal ileum was found. Histopathological examination of the resected part of ileum revealed compatibility with GIST. It was strongly positive for cluster of differentiation 117 (CD117) and smooth muscle actin. Patient received adjuvant therapy with Imatinib. A complete surgical resection without extensive lymph node sampling is the primary treatment option. As GIST are rare, a high index of suspicion is warranted for diagnosis and appropriate treatment.